The Mechanisms of Type 2 Diabetes-Related White Matter Intensities: A Review - Sun, Jing; Xu, Baofeng; Zhang, Xuejiao; He, Zhidong; Liu, Ziwei; Liu, Rui; Nan, Guangxian (Frontiers in Public Health, 2020)
The continually increasing number of patients with type 2 diabetic is a worldwide health problem, and the incidence of microvascular complications is closely related to type 2 diabetes. Structural brain abnormalities are considered an important pathway through which type 2 diabetes causes brain diseases. In fact, there is considerable evidence that type 2 diabetes is associated with an increased risk of structural brain abnormalities such as lacunar infarcts (LIs), white matter hyperintensities (WMHs), and brain atrophy. WMHs are a common cerebral small-vessel disease in elderly adults, and it is characterized histologically by demyelination, loss of oligodendrocytes, and vacuolization as a result of small-vessel ischemia in the white matter. An increasing number of studies have found that diabetes is closely related to WMHs. However, the exact mechanism by which type 2 diabetes causes WMHs is not fully understood. This article reviews the mechanism of type 2 diabetes-related WMHs to better understand the disease, and provide help for better clinical treatment.